A CULTURALLY SENSITIVE APPROACH IN HEALTH LAW TO BUILD TRUST BETWEEN PATIENTS AND MEDICAL PERSONNEL AND IMPROVE THE QUALITY OF HOSPITAL SERVICES: A LITERATURE REVIEW - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study discusses a culturally sensitive approach in the context of health law as an effort to build trust between patients and medical personnel and improve the quality of hospital services. A culturally sensitive approach in health law focuses on recognising, respecting, and protecting the cultural diversity of patients in the medical service process, which in turn strengthens therapeutic relationships and creates an inclusive and responsive service environment. A literature review method was used to analyse various studies and regulations relevant to the integration of cultural values in health law practice and its implications for patient trust and service quality. The results of the review show that the application of a culturally sensitive approach significantly increases patient trust through more effective communication, respect for cultural values, and reduced discrimination. The trust that is built has a positive impact on treatment compliance, patient satisfaction, and loyalty to the hospital. In addition, the quality of hospital services becomes more humane and in line with the cultural needs of patients, which contributes to the positive reputation of the institution and the sustainability of services. In conclusion, the integration of a culturally sensitive approach in health law is a key strategy in building a fair, inclusive, and high-quality healthcare system. This study highlights the importance of developing legal regulations and cultural competency training for medical personnel to address the needs and challenges of cultural diversity in modern healthcare. Practical implications are suggested for policymakers and hospitals to continue optimising the application of these principles in order to improve trust and service quality in a sustainable manner.